Introduction of Post-Ecological Poetry - Park, Dong Eok (International Journal of Korean Humanities and Social Sciences, 2024)
This paper explores contemporary Korean poetry through two distinct ecological perspectives. First, it reflects on the anthropocentrism inherent in conventional ecological poetry. Second, it investigates the potential for a post-ecological poetry that transcends this anthropocentrism. Traditional nature poetry aims to address ecological concerns but often relies on an anthropocentric perspective shaped by human-centered views. This tendency reduces nature to an aesthetic and comforting entity for human consumption. Despite the poet’s sincere ecological intentions, ecological poetry often risks emphasizing the poet’s ethical superiority rather than fostering a deeper connection with nature. In contrast, poets like Kim Hye-soon (김혜순) and Heo Soo-kyung (허수경) have acknowledged the limitations of conventional ecological poetry and experimented with new poetic forms by incorporating hybrid perspectives, blending human and non-human voices, and addressing ecological issues through innovative structures and metaphors. This paper defines their works as post-ecological poetry and seeks to examine the significance of these creations.